Get an answer in 5 minutes
We'll notify as soon as your question has been answered.
How do we do this? First, find the difference between the two x & y co-ordinates: y² - y¹ = (1 - -5) = 6 x² - x¹ = (0 - -2) = 2 So we now know that for every 6 times y increases, x increases by 2. We can simplify to y being 3 times x. So: Y=3x + c. Now solve for c: Plug in any of the given co-ordinates for x & y: (-5) = 3(-2) + c. OR: (1) = 3(0) + c :. -5 = -6 + c. OR: 1 = c Therefore Y = 3x + 1
Asked by Brittany Ashtherielle
What is the example of a sequence using 3n nth term